2020
DOI: 10.1007/s10342-020-01289-1
|View full text |Cite
|
Sign up to set email alerts
|

Foliar P nutrition of European beech (Fagus sylvatica L.) depends on the season but remains unaffected by co-cultivation with silver fir (Abies alba Mill.)

Abstract: Beech (Fagus sylvatica) and silver fir (Abies alba) are often cultivated in mixed stands and, hence, compete for water and nutrients. Besides nitrogen (N), also phosphorus (P) is an important nutrient for growth and development. Beech trees in Central Europe grow on both P-poor and P-rich soils, thereby showing similar growth and low variation in foliar P. The central aim of the present study was to test the hypothesis that variations in foliar P contents of beech are driven by seasonal changes rather than by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 82 publications
3
5
0
Order By: Relevance
“…The total N contents observed in this study were in the range previously found in European beech and fir [33,53,[87][88][89]. They were largely conserved in the year subsequent to water deprivation in beech, due to stable protein contents, which is the main cytoplasmic N pool in this species [18,33,88,89]. Therefore, our second hypothesis, that memory effects are established in both leaves and roots as altered C and N contents, is only supported for C, but not for N.…”
Section: Memory Effects On Carbon and Nitrogen Metabolismsupporting
confidence: 61%
See 2 more Smart Citations
“…The total N contents observed in this study were in the range previously found in European beech and fir [33,53,[87][88][89]. They were largely conserved in the year subsequent to water deprivation in beech, due to stable protein contents, which is the main cytoplasmic N pool in this species [18,33,88,89]. Therefore, our second hypothesis, that memory effects are established in both leaves and roots as altered C and N contents, is only supported for C, but not for N.…”
Section: Memory Effects On Carbon and Nitrogen Metabolismsupporting
confidence: 61%
“…Compared to C dynamics, information on post-stress responses of N contents and partitioning in trees is extremely scarce, despite this knowledge being of particular importance for predicting the resilience of forests under climate change conditions [31,86]. The total N contents observed in this study were in the range previously found in European beech and fir [33,53,[87][88][89]. They were largely conserved in the year subsequent to water deprivation in beech, due to stable protein contents, which is the main cytoplasmic N pool in this species [18,33,88,89].…”
Section: Memory Effects On Carbon and Nitrogen Metabolismsupporting
confidence: 53%
See 1 more Smart Citation
“…Our temporal models for beech LMTs indicate a positive effect of foliar N concentration on DM100 and LA and a negative effect of foliar Ca and P concentrations on LA and LMA (Table 4). N is the most important and growth-limiting nutrient in beech trees in temperate forests (Yang et al, 2020), and the positive effect of foliar N concentration on DM100 and LA is in line with the knowledge that foliar N concentrations increase linearly with the photosynthetic capacity per unit leaf mass (Chapin and Eviner, 2004). The interpretation of the negative relationship of foliar Ca and P with LA and LMA is less straightforward.…”
Section: Foliar Nutrient Effects On Leaf Morphological Traitssupporting
confidence: 54%
“…Plant P status has multiple effects in almost all aspects of plant metabolism, and there is insufficient knowledge on the effects of P deficiency on metabolite levels in evergreen trees ( Warren, 2011 ; Netzer et al, 2018 ; Yang et al, 2020 ). In the present study, the hierarchical cluster analysis of primary metabolites from leaves differentiated E. acmenoides from the other species.…”
Section: Discussionmentioning
confidence: 99%